Potensi Ekstrak Tanaman Sebagai Pestisida Alami Di Desa Salu Kecamatan Miomafo Barat Kabupaten TTU - Jefry Presson; Gebhardus D Gelyaman; Yohana Ivana Kedang; Sefrinus Maria D. Kolo; Regina Seran; Eduardus Edi; Maria Magdalena Kolo (LPPM Universitas Timor, 2019)
Devotion with the title of potential plant extracts as natural pesticides in Salu village, Miomafo Barat district, TTU district was held in November 2018. The purpose of this service was to provide knowledge on how to increase food production through eradicating pests, providing knowledge about the advantages of natural pesticides compared to synthetic pesticides, and make soursop leaf extract as a natural pesticide. The main target of this activity is the farmers who are conducted through methods of lecture, brochure distribution, and product manufacturing training. This service activity was conducted in 3 sessions. The first session was socialization of ways to increase food production through eradicating pests. The second session is a socialization of the advantages of natural pesticides compared to synthetic pesticides. Making soursop extract as a natural pesticide is the third session that closes all the series of devotion. In addition to providing questions, farmers also provide personal experiences that are useful for the development of science. The coordination of the making of soursop extract indicates the high enthusiasm of the farmers in Salu village towards this devotion. The final product in this activity is soursop leaf extract which is ready to be applied to plants.